Studying Russia and its Wars : Academic Stocktaking in Times of Insecurity - Kurnyshova, Yuliia,; Makarychev, Andrey, (Social Sciences E-Books Online, Collection 2026., 2026)
Russia's invasion of Ukraine took by surprise not only politicians in many countries, but also experts who, for many years after the end of the Cold War, were confident of the growing mutual interdependence between Russian and European economies, and in the changing function of borders - from dividing to connecting. Most scholars have not only overlooked the aggressive potential inherent in the seemingly innocent calls for multipolarity carried out by the Russian leadership. This book discusses how the current war in Ukraine makes the scholarly community reconsider previous assumptions of Russia's domestic regime and security policies, and think of novel approaches to study the Russia-produced insecurities. This edited volume calls for a scholarly audit of the academic legacy that has prevented most researchers and public intellectuals from not only predicting, but also considering as a serious possibility the full-scale war that Russia unleashed against Ukraine. Contributors are: Françoise Daucé, Dinissa Duvanova, Vladimir Gelman, Ivan Gomza, Sanshiro Hosaka, Ailaksei Kazharski, Ivan U. Kłyszcz, Yulia Kurnyshova, Andrey Makarychev, Katalin Miklóssy, Anselm Schmidt, and Kirill Shamiev.